A2.20 Synovial FCRl4+ B cells are enriched in citrulline reactivity without displaying signs of differentiation to a plasma cell phenotype. (24th February 2016) - Amara, K; Clay, E; Yeo, L; Ramsköld, D; Spengler, J; Sippl, N; Israelsson, L; Titcombe, P; Grönwall, C; Filer, A; Raza, K; Malmström, V; et al.
Abstract : Background and objectives: Expression of Fc Receptor like 4 (FcRL4) identifies a memory B cell subset, which is enriched in the joints of patients with rheumatoid arthritis (RA) and in mucosa associated lymphoid tissue. Their high level of RANKL production indicates a unique pathogenic role. Here, B cell receptor characteristics, antigen specificity and transcriptomic profile of FcRL4 + B cells sorted from the joints of RA patients were investigated. Materials and methods: FcRL4 + and FcRL4 - B cells were sorted from synovial fluid (SF) and tissue of patients with active RA. Their immunoglobulin variable region (IgVH) genes were sequenced and expressed to generate recombinant monoclonal antibodies (mAbs). Reactivity of 63 mAbs towards native and citrullinated peptides derived from α-enolase, fibrinogen, vimentin, histones 3 and 4 was determined by ELISA and Phadia's ImmunoCAP ISAC microarray system. RNA sequencing was carried out on sorted SF FcRL4 + and FcRL4 - B cells. After preamplification using the SMARTer amplification kit, library preparation was carried out using Illumina's TruSeq Stranded prep and sequenced on the Illumina platform. Data analysis was carried out using the programs rna-star, DESeq2 and ToppGene. Results: Analysis of IgVH genes usage in FcRL4 + and FcRL4 - B cells indicated that the Ig repertoire was highly diverse in both B cell subsets, however VH1–69 gene segment was significantly over-represented in the FcRL4 + B cell population (P = 0.013). Out of the 63 mAbs tested, eight antibodies displayed high level of binding to citrullinated peptides. These were exclusively derived from the FcRL4 + subset (p = 0.018). Another eleven antibodies showed low levels of binding to citrullinated peptides. These were derived from both FcRL4 + and FcRL4 - B cells. Global transcriptome analysis showed clear differences between the two B cell subsets, including 64 genes which were significantly over or under-expressed in FcRL4 + B cells. Among the genes underexpressed in FcRL4+ B cells, the majority were associated with antibody production and plasma cell differentiation. Conclusions: Reactivity of FcRL4 + B cells towards citrullinated autoantigens suggests that they are a component of the citrulline-specific autoimmune response, however, their low level of expression of immunoglobulin and plasma cell differentiation genes suggests functions alternative to antibody production.